Determination of reinforcement depth for low-energy dynamic compaction construction in high-fill engineering in mountainous areas - XIAOBING, Cheng; DZHEDZHULA, Viacheslav (Ways to Improve Construction Efficiency, 2025)
Dynamic compaction technology has gained rapid development and widespread application in soft soil reinforcement due to its numerous advantages. This study investigates low-energy dynamic compaction commonly used in high-fill mountain engineering, detailing its construction processes and engineering applications while systematically reviewing current theories and advancements in determining reinforcement zones. However, existing methods for defining effective reinforcement depth still rely heavily on construction experience and trial section testing, resulting in cumbersome procedures, high data dispersion, and insufficient reliability. To address this, the authors established a clear distinction between "effective reinforcement depth" and "influence depth of reinforcement" based on the "ellipsoidal morphology" assumption. Starting from the principle of equal soil mass before and after compaction (neglecting air mass), a complete set of calculation formulas for both depths was derived. The derivation process incorporated both compaction parameters (e.g., energy level, tamping frequency) and intrinsic soil properties (e.g., initial density, Poisson’s ratio). These formulas enable efficient computation of reinforcement depths when inputting known parameters, offering a novel approach to evaluate reinforcement effectiveness and optimize compaction strategies for low-energy projects. Furthermore, a series of low-energy dynamic compaction tests with varying energy levels were designed and implemented in a northwestern Chinese high-fill project. Field measurements of single-blow and cumulative settlements, effective reinforcement depths, and influence depths were collected and compared with formula-calculated results, confirming the formulas’ accuracy and engineering reliability. The methodology and outcomes provide a research paradigm for similar projects and enrich the theoretical basis for evaluating soft soil reinforcement using dynamic compaction technology.